The Isolation and Identification of Bacterial Strains native bioremediation Environments and their Application in the Cultivation of Litopenaeus Vannamei White Shrimp. (Revista Científica Ciencias Naturales y Ambientales, 2012)
This study aimed to isolate and identify potential bacteria from soil biorremediadora two Shrimp pools A in the Province of El Oro. Biorremediadora capacity of seven morphotypes in shrimp farming in the pools was evaluated by testing the application of two probiotic bacteria made with BSM1 (Bacillus sp), BSM2 Bacillus sp), BSM3 (Pseudomonas sp), BSM7 (Lactobacillus plantarum), BMS8 (Pseudomonas sp), BMS10 (Lactobacillus plantarum), BMS11 (Bacillus sp) and yeast (Sacharomyces serevisae). The results showed that the bioremediation of soil, water and shrimp pools testing of Shrimp pools One and Two inthe first production was the same as the pools control, in the second and third production were higher. The presence of pathogenic bacteria, there was no evidence in any of the controls in the study pools. The application of probiotics native positively influenced the increase in survival, weight gain, feed conversion and shrimp pounds per acre at harvest, which showed statistically significant differences for the days of evaluation period of the investigation.
Keywords: Probiotics; BSM; shrimp